Is participatory leadership conducive to the construction of virtual teams? Based on multi-agent simulation model - Liu, Ruonan; Huang, Zhenyu (Frontiers in Psychology, 2022)
With the continuous improvement of the technical level, the virtual teams are constantly evolving, the relationship between leadership and the construction of virtual teams has received more and more attention. It is of great significance to explore the influence of participatory leadership on the construction of virtual teams from a psychological perspective by building a multi-agent simulation model. Based on a simulation platform of Netlogo, the results showed that: (1) Participatory leadership is conducive to the expansion of the scale of virtual teams by providing greater space for development for the members of virtual teams and meeting the team members’ requirements of planning and promotion in the environment, which is decentralized and non-authoritative. (2) However, the loosing management is not conducive to build a reasonable structure of team member under the participatory leadership. (3) The scale of virtual teams and the efficiency of the virtual teams all depend on the relationship among the participatory leadership, organizational trust, incentive mode, and the balance of cooperation and competition.